STUDENTS’ KNOWLEDGE AND PERCEPTION TOWARDS ASYNCHRONOUS BLENDED PROBLEM-BASED LEARNING - Yuniar Dwi Yanti; Mieke Hemiawati Satari; Ike Rostikawati Husen (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Lecture is a dominant learning method that still used in teaching process. This method only focuses to lecturer and does not involving students’ participation enough. Problem Based Learning (PBL) is a learning method that could activate students’ participation, but it has many obstacles on its implementation. Asynchronous blended problem-based learning (ABLE PBL) is an innovative learning method that adopts (Problem Based Learning) PBL learning principles and it is expected to reduce problems in implementing PBL. This study was conducted to analyze the students’ knowledge between ABLE PBL method and lecture and to describe students’ perceptions towards ABLE PBL.Methods: A modified crossover design was conducted to determine students’ knowledge and descriptive study for students’ perception among a total sampling of 44 students who enrolled the third semester at Departement of Midwifery, Diploma Program at Dharma Husada Bandung Health College. It used Mann Whitney test to analyze students’ knowledge to each chapterResult: The result showed that there is no difference significantly of students’ knowledge between two groups for both chapters, ABLE PBL does not influence students’ knowledge but students’s perception about ABLE PBL is positive because the respondent experienced new method of learning. Conclusion: In conclusion, there are no differences between two groups significantly for each chapter with p value bigger than 0.05, yet ABLE PBL could give a positve perception to students.